FOOD ALLERGIES IN CHILDREN: RISK FACTORS AND CLINICAL FEATURES (Conferencea, 2022)
According to the position of EAACI, in the coming years, an increase in the prevalence of allergies caused by sensitization to aeroallergens is expected, due to changes not only in sensitizing structures, but also in food preferences (annual replenishment of the diet with exotic fruits and vegetables, long-term transportation and storage of products), entailing the emergence of new, as yet undescribed, cross-reactions [3].